Pengaruh Independensi, Objektivitas, Integritas Dan Kompetensi Terhadap Kualitas Hasil Audit (Studi Kasus Pada Kantor Akuntan Publik Kota Medan) - Saputra, Muhammad Ilham; Siregar, Saparuddin; Nasution, Juliana (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine the Effect of Independence, Objectivity, Integrity and Competence on the Quality of Audit Results (Case Study at the Medan City Public Accounting Firm). The method used is a quantitative method. And the sample in this study used the proportional stratified random sampling method, which is a method by linking the sampling of each population whose number is adjusted to the number of members of each population, with a total of 53 respondents from 9 Public Accounting Firms in the city of Medan. The data collection instrument used a questionnaire or a questionnaire that was tested for validity and reliability. Data analysis techniques using multiple linear regression, hypothesis testing, t test, F test and the coefficient of determination. With the results of research, independence affects the quality of audit results. Objectivity affects the quality of audit results. Integration affects the quality of audit results. Competence affects the quality of audit results. independence, objectivity, integrity and competence simultaneously affect the quality of audit results.